ORIENTASI PEMBELAJARAN ORGANISASI SEBAGAI ANTESEDEN INOVASI ORGANISASI - Hendriyanto, Asepta (STIE Totalwin Semarang, 2013)
Contemporary organizations require a strong learning orientation to gain competitive advantage. Based on a review of the literature, the present investigation delineates four components of learning orientation: commitment to learning, shared vision, open-mindedness, and intraorganizational knowledge sharing. Learning orientation is conceptualized as a second-order construct. Its effect on firm innovativeness is examined